Structure‐Activity Relationship of Defective Metal‐Based Photocatalysts for Water Splitting: Experimental and Theoretical Perspectives - Yong‐Chao Zhang; Nisha Afzal; Lun Pan; Xiangwen Zhang; Ji‐Jun Zou (Advanced Science, 2019)
Abstract Photocatalytic water splitting is promising for hydrogen energy production using solar energy and developing highly efficient photocatalysts is challenging. Defect engineering is proved to be a very useful strategy to promote the photocatalytic performance of metal‐based photocatalysts, however, the vital role of defects is still ambiguous. This work comprehensively reviews point defective metal‐based photocatalysts for water splitting, focusing on understanding the defects' disorder effect on optical adsorption, charge separation and migration, and surface reaction. The controllable synthesis and tuning strategies of defective structure to improve the photocatalytic performance are summarized, then the characterization techniques and density functional theory calculations are discussed to unveil the defect structure, and analyze the defects induced electronic structure change of catalysts and its ultimate effect on the photocatalytic activity at the molecular level. Finally, the challenge in developing more efficient defective metal‐based photocatalysts is outlined. This work may help further the understanding of the fundamental role of defect structure in the photocatalytic reaction process and guide the rational design and fabrication of highly efficient and low‐cost photocatalysts.